Economic impact of biological control of water hyacinth in southern Benin - Groote, H. de; Ajuonu, O.; Attignon, S.; Djessou, R.; Neuenschwander, Peter (Elsevier, 2003)
A biological control program of water hyacinth was undertaken in Southern Benin between 1991 and 1993. It consisted of the release of three natural enemies, two weevil species and one moth, that feed exclusively on water hyacinth. In 1999, a survey of 365 men and women from 192 households in 24 villages in the target area, using participatory and quantitative methods, revealed that water hyacinth, although not eliminated, was perceived by the villagers as having been reduced from a serious pest to one of minor or moderate importance. According to their estimates of the impacts they perceived, at the peak of the infestation water hyacinth had reduced the yearly income of this population of about 200 000 by approximately US$84 million. Lost revenues for men were mostly in fishing, while women experienced lost revenues in trade, primarily food crops and fish. The reduction of water hyacinth cover through biological control was credited with an increase in income of US$30.5 million per year. The total cost of the control program is estimated at a present value of US$2.09 million. Assuming the benefits are to stay constant over the next 20 years, a most conservative assumption, the accumulated present value would be US$260 million, yielding a respectable benefit cost ratio of 124:1. This ratio is calculated for direct economic effects on the people of Southern Benin only, and does not take into account indirect benefits or the benefits of the project to other countries were the biological control agents were successfully introduced. Other effects mentioned, but not measured, included an increase of water quality and of human health.